Quartet of truths in the philosophy of Badiou - Wasilewski, Andrzej (Hybris, 2017)
Alain Badiou is one of the most popular French philosophers. He created the ontological system based on renovated concepts of being, truth, and subject. In this way he refers to the classical philosophy. The current article intends to introduce the reader to Badiou's theory of truth. He opposed correspondence theory. He believes that a truth has nothing to do with the statements about the actual state of affairs. Truth is the result of the process, the final effect of the generic procedures. There are only four types of such procedures, which produce the truths: scientific, artistic, political, and amorous. The main aim of this work is to characterize every kind of truth.